Roles of retinoic acid signaling in normal and abnormal development of the palate and tongue. (May 2014) - Okano, Junko; Udagawa, Jun; Shiota, Kohei
Abstract Palatogenesis involves various developmental events such as growth, elevation, elongation and fusion of opposing palatal shelves. Extrinsic factors such as mouth opening and subsequent tongue withdrawal are also needed for the horizontal elevation of palate shelves. Failure of any of these steps can lead to cleft palate, one of the most common birth defects in humans. It has been shown that retinoic acid (RA) plays important roles during palate development, but excess RA causes cleft palate in fetuses of both rodents and humans. Thus, the coordinated regulation of retinoid metabolism is essential for normal palatogenesis. The endogenous RA level is determined by the balance of RA‐synthesizing (retinaldehyde dehydrogenases: RALDHs) and RA‐degrading enzymes (CYP26s). Cyp26b1 is a key player in normal palatogenesis. In this review, we discuss recent progress in the study of the pathogenesis of RA‐induced cleft palate, with special reference to the regulation of endogenous RA levels by RA‐degrading enzymes.